Investment in education : the implications for economic growth and public finances - Montanino, Andrea; Przywara, Bartosz; Young, David; European Commission : Directorate-General for Economic and Financial Affairs (Brussels ; Belgium : European Commission: Directorate-General for Economic and Financial Affairs, 2004)
This paper analyses the demographic and institutional influences underlying public spending on education, as well as the consequences for average educational attainment and economic growth. The issues are topical given, on one hand, EU objectives for increased investment in human resources and, on the other, increasing concerns about the sustainability of public finances, particularly in view of ageing populations. The paper presents methodologies for projecting educational attainment and public expenditure on education. Tentative numerical results suggest that the growth of average educational attainment is likely to slow slightly, compared to recent decades. Nevertheless, education is set to continue making a substantial contribution to economic growth in the EU as a whole, though the impact varies widely among Member States. As regards public expenditure, although demographic trends mean a reduction in the potential number of students, this is offset by two factors: increasing enrolment rates at upper-secondary and tertiary level (projected taking into consideration either past developments in enrolment or the expected future evolution of labour force); and increasing expenditure per student (projected on the basis of recent trends). Thus, few savings - if any - are expected from reductions in expenditure on education due to changes in the demographic structure.
Economic Papers